Asas-Asas Pendidikan Dalam Alquran dan Kedudukan Manusia Dalam Alam Semesta - Lydia Sartika (Universitas Islam Negeri Sumatera Utara, 2020)
This study aims to determine the principles of education in the Quran and the position of humans in the universe. This study uses a qualitative approach. The data were collected using the interview method which was conducted on the students, teachers, principals and education practitioners. The sample used was snowball sampling. The conclusion can be stated that according to the philosophy of Islamic education humans are alternative beings (free) but at the same time bound (not free of value). A principle is based on Islamic education if it has components of integration, balance, equality, lifelong education and virtue. Meanwhile, various educational principles in the Koran include religious, historical, social, philosophical, early childhood education and economic principles. Islam views the existence of the universe or Allah created the universe to fulfill human interests. Therefore, the universe becomes the source, material, method, media and environment in order to realize the purpose of human life through the realization of the goals of Islamic education that are identical to the goals of life. The Koran does not view humans as creatures that were created by chance, or created from a collection of atoms, but they were created after being planned to carry out a task as caliph on this earth. The proper way to develop and maintain human nature as caliph on earth is through education, because education (al-Tarbiyah) includes various dimensions, namely body, mind, feelings, will and all human psychological elements as well as talents and abilities.